The Calcutta couples : a biosocial profile - Pakrasi, Kanti B., 1926-; Banerjee, Amulya Ratan; Halder, Ajit K. (Ajit Kumar), 1928- (Editions Indian, 1980)
Contributed papers on family building and planning.